The Association of Financial Inclusion and Multidimensional Energy Poverty in Indonesia - Aprilina Tri Widyastuti; Djoni Hartono (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
Financial service could reduce household energy poverty through fund transfer to encourage the ability to access modern energy. This study investigate the role of financial inclusion on household energy poverty in Indonesia. The energy poverty variable is measured by using multidimensional approach with five dimensions and six indicators which are cooking fuels, indoor pollution, lighting, ownership of household appliances, and supporting equipment for basic services such as education, entertainment, and communication. Financial inclusion is measured by using multidimensional approach based on household accessibility to financial institution such as banking, credit, and insurance services. Linear Probability Model (LPM) and Probit model was used to investigate the association between financial inclusion and energy poverty. The result finds that financial inclusion has a negative association with household energy poverty. It implicates strategy for reduce energy poverty by increase financial access such as bank agents, especially in areas which far from banks.How to cite:Widyastuti, A. T., & Hartono, D. (2022). The Association of Financial Inclusion and Multidimensional Energy Poverty in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 201-218. https://doi.org/10.15408/sjie.v11i2.26516.